Why renewable energy could be a chance for the GCC economies - El-Katiri, L (Oxford Institute for Energy Studies, 2014)
The GCC economies have come a long way since the onset of the age of oil. When the first oil well was struck in Jebel Dukhan in Bahrain in 1931, few would have forecast that the fortunes of the sheikhdoms along the Gulf would be so fundamentally shaped by a single energy commodity as has turned out to be the case. Today’s wealth, visible in the global capital cities Riyadh, Abu Dhabi, and Kuwait City, is as much the result of the region’s unique gift of natural resources as it is of historical leadership in the use of these resources in promoting the region’s unparalleled economic development. Safeguarding this wealth will also, in the future, require answers to strategic questions; these include how to prioritize between the domestic value of regional oil and gas resources and their marginal export value, in view of the GCC economies’ own rapidly rising domestic energy needs. Renewable energy sources could form an important part of the answer to such questions, provided they are used in a clever way.